Berpikir & menjadi sukses penuntun pribadi anda menuju kemandiria.. David J. Schwartz ; alih bahasa, Anton Adiwiyoto ; editor, Lyndon Saputra - SCHWARTZ, David J; Saputra, Lyndon; Adiwiyoto, Anton (1996)
403 hlm 18 cm